Biallelic variant in AGTPBP1 causes infantile lower motor neuron degeneration and cerebellar atrophy. Issue 8 (18th May 2019) - Karakaya, Mert; Paketci, Cem; Altmueller, Janine; Thiele, Holger; Hoelker, Irmgard; Yis, Uluc; Wirth, Brunhilde
Abstract: Infantile hereditary lower motor neuron disorders beyond 5q–spinal muscular atrophy (5q‐SMA) are usually caused by mutations other than deletions or mutations in SMN1 . In addition to motor neuron degeneration, further neurologic or multisystemic pathologies in non‐5q‐SMAs are not seldom. Some of the non‐5q‐SMA phenotypes, such as pontocerebellar hypoplasia (PCH1), have been classified later as a different disease group due to distinctive primary pathologies. Likewise, a novel phenotype, childhood‐onset neurodegeneration with cerebellar atrophy (CONDCA) has been described recently in individuals with lower motor neuron disorder and cerebellar atrophy due to biallelic loss‐of‐function variants in AGTPBP1 that encodes cytosolic carboxypeptidase 1 (CCP1). Here we present two individuals with CONDCA in whom a biallelic missense AGTPBP1 variant (NM_001330701.1:c.2396G>T, p.Arg799Leu) was identified by whole exome sequencing. Affected individuals in this report correspond to the severe infantile spectrum of the disease and underline the severe pathogenic effect of this missense variant. This report is the second in the literature that delineates the pathogenic effects of biallelic AGTPBP1 variants presenting the recently described CONDCA disease.